Adult Hippocampal Neurogenesis and Plasticity in the Infrapyramidal Bundle of the Mossy Fiber Projection: II. Genetic Covariation and Identification of Nos1 as Linking Candidate Gene - Krebs, Julia; Römer, Benedikt; Overall, Rupert W.; Fabel, Klaus; Babu, Harish; Brandt, Moritz; Williams, Robert W.; Jessberger, Sebastian; Kempermann, Gerd (Frontiers in Neuroscience, 2011)
The hippocampus of adult rodents harbors two systems exhibiting structural plasticity beyond the level of synapses and dendrites. First, the persistent generation of granule cells (adult neurogenesis); second, dynamic changes in the mossy fibers, in particular in the infrapyramidal mossy fiber (IMF) tract. Because mossy fibers are the axons of granule cells, the question arises whether these two types of plasticity are linked. In the first arm of this study (Römer et al., Frontiers in Neurogenesis #ref#) we have asked how both traits are regulated in relation to each other. In the present study, we asked whether, besides activity-dependent co-regulation, there would also be signs of genetic co-regulation and co-variance. For this purpose we used the BXD panel of recombinant inbred strains of mice, a unique genetic reference population that allows genetic association studies. In 31 BXD strains we did not find correlations between the traits describing the volume of the mossy fiber subfields and measures of adult neurogenesis. When we carried out quantitative trait locus mapping for these traits, we found that the map for IMF volume showed little overlap with the maps for the other parts of the projection or for adult neurogenesis, suggesting that to a large degree the IMF is regulated independently. The highest overlapping peak in the genome-wide association maps for IMF volume and the number of new neurons was on distal chromosome 5 (118.3–199.2 Mb) with an LRS score of 5.5 for IMF and 6.0 for new neurons. Within this interval we identified Nos1 (neuronal nitric oxide synthase) as a cis-acting (i.e. presumably autoregulatory) candidate gene. The expression of Nos1 is has been previously linked with both IMF and adult neurogenesis, supporting our findings. Despite explaining on its own very little of the variance in the highly multigenic traits studied, our results suggest Nos1 may play a part in the complex genetic control of adult neurogenesis and IMF morphology.